2017
DOI: 10.1126/science.aao1583
|View full text |Cite
|
Sign up to set email alerts
|

Crystal structure of the human lysosomal mTORC1 scaffold complex and its impact on signaling

Abstract: The LAMTOR [late endosomal and lysosomal adaptor and MAPK (mitogen-activated protein kinase) and mTOR (mechanistic target of rapamycin) activator] complex, also known as "Ragulator," controls the activity of mTOR complex 1 (mTORC1) on the lysosome. The crystal structure of LAMTOR consists of two roadblock/LC7 domain-folded heterodimers wrapped and apparently held together by LAMTOR1, which assembles the complex on lysosomes. In addition, the Rag guanosine triphosphatases (GTPases) associated with the pentamer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
96
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(106 citation statements)
references
References 59 publications
8
96
0
2
Order By: Relevance
“…The structure of Ragulator alone appears to be essentially the same as ours, reinforcing confidence in the accuracy of these structures. In the presence of the roadblock domains of RagA/C, Lamtor1 residues after 47 were found to be well ordered (de Araujo et al, 2017), consistent with our observation of HDX protection for Lamtor1 residues 61-70 in the presence of RagA/C. Interacting residues, such as Lamtor1 Val148, mutated in this study reduce function, consistent with expectations from our structure.…”
Section: Lamtor3supporting
confidence: 91%
See 2 more Smart Citations
“…The structure of Ragulator alone appears to be essentially the same as ours, reinforcing confidence in the accuracy of these structures. In the presence of the roadblock domains of RagA/C, Lamtor1 residues after 47 were found to be well ordered (de Araujo et al, 2017), consistent with our observation of HDX protection for Lamtor1 residues 61-70 in the presence of RagA/C. Interacting residues, such as Lamtor1 Val148, mutated in this study reduce function, consistent with expectations from our structure.…”
Section: Lamtor3supporting
confidence: 91%
“…In spite of the limited resolution of the EM structure, the orientation deduced for the RagA/C dimer relative to Ragulator is very similar. Similar conclusions were drawn based on the two different approaches applied, EM reconstruction with a full-length active RagA/C dimer in this case, and crystallization with the RagA/C roadblock fragments in the other study (de Araujo et al, 2017). The structural insights presented in these two studies will set the stage for a more detailed analysis of how the active Rag:Ragulator complex recruits and activates mTORC1, a central question at the heart of much current research into cellular metabolic regulation.…”
Section: Lamtor3supporting
confidence: 69%
See 1 more Smart Citation
“…At 16 Å, RagA and RagC appear essentially identical, and the assignment of RagA to one side and RagC to the other was ambiguous. On the basis of the report by de Araujo (2017), the assignment shown in Fig. 5C was selected.…”
Section: Resultsmentioning
confidence: 99%
“…While the initial version of this manuscript was under review, Scheffzek and colleagues reported the crystal structure of Ragulator alone and bound to the roadblock domains of RagA/C (de Araujo et al, 2017). The structure of Ragulator alone appears to be essentially the same as ours, reinforcing confidence in the accuracy of these structures.…”
Section: Discussionmentioning
confidence: 99%